Elevated platelet-leukocyte complexes are associated with, but dispensable for myocardial ischemia-reperfusion injury - Starz, Christopher; Härdtner, Carmen; Mauler, Maximilian; Dufner, Bianca; Hoppe, Natalie; Krebs, Katja; Ehlert, Carolin Anna; Merz, Julian; Heidt, Timo; Stachon, Peter; Wolf, Dennis; Bode, Christoph; et al. (Basic research in cardiology, 2022)
P-selectin is an activatable adhesion molecule on platelets promoting platelet aggregation, and platelet-leukocyte complex (PLC) formation. Increased numbers of PLC are circulating in the blood of patients shortly after acute myocardial infarction and predict adverse outcomes. These correlations led to speculations about whether PLC may represent novel therapeutic targets. We therefore set out to elucidate the pathomechanistic relevance of PLC in myocardial ischemia and reperfusion injury.
Gesehen am 11.01.2023